O ESTADO AMBIENTAL COMO INDICADOR NA QUALIDADE DE VIDA DA POPULAÇÃO: uma análise da relação saúde e ambiente no centro urbano do município de Raposa, Maranhão, Brasil. - Silva, Luciney de Jesus Costa da (2008)
It is analyzed the relation health and environment in the urban space of the Raposa (MA) borough, beginning for the discussion of some environmental problems of general and specific character. It is done a bibliography analysis about the interaction human and environmental, discussing the environmental quality and environmental degradation; about the relation health and society, where it is accosted also the environmental health and the life quality. This analysis lectures about the source and creation of Raposa borough, besides the physiographic aspects. It is Studied the relation between environmental condition of the urban solo and the life quality. The socioeconomic situation is diagnosed, as the urban infrastructure, population s composition and economic situation; environmental situation, how the degradation, the environmental insanitariness and the water s quality consumed trough microbiological analysis; the sanitary situation, how the Health s Family Program performance and the official sanitary statistics of Raposa borough.